Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1371/journal.pmed.1002919
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, social, and welfare interventions for torture survivors: A systematic review and meta-analysis of randomised controlled trials

Abstract: BackgroundTorture and other forms of ill treatment have been reported in at least 141 countries, exposing a global crisis. Survivors face multiple physical, psychological, and social difficulties. Psychological consequences for survivors are varied, and evidence on treatment is mixed. We conducted a systematic review and meta-analysis to estimate the benefits and harms of psychological, social, and welfare interventions for torture survivors.Methods and findingsWe updated a 2014 review with published randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Evaluating nine studies of cognitive behavioural therapy (CBT) and narrative exposure therapy (NET) with torture survivors, a Cochrane review found no immediate posttreatment effect. In contrast, three NET studies, and a CBT study elicited medium effect sizes on trauma symptoms at six-month follow-up (Patel, Kellezi, & Williams, 2014), while a meta-analysis of torture survivors found that psychological interventions significantly reduced PTSD symptoms by the end of treatment, with a small SMD that remained at follow-up (Hamid, Patel, & Williams, 2019). Recently, three recent systematic reviews of the treatment of refugees and asylum seekers resettled in highincome countries have demonstrated the efficacy of psychosocial interventions on PTSD symptoms (Nosè et al, 2017;Thompson, Vidgen, & Roberts, 2018;Turrini, Purgato, Acarturk, & Anttila, 2019).…”
Section: Treatment Of Traumatized Refugeesmentioning
confidence: 89%
See 1 more Smart Citation
“…Evaluating nine studies of cognitive behavioural therapy (CBT) and narrative exposure therapy (NET) with torture survivors, a Cochrane review found no immediate posttreatment effect. In contrast, three NET studies, and a CBT study elicited medium effect sizes on trauma symptoms at six-month follow-up (Patel, Kellezi, & Williams, 2014), while a meta-analysis of torture survivors found that psychological interventions significantly reduced PTSD symptoms by the end of treatment, with a small SMD that remained at follow-up (Hamid, Patel, & Williams, 2019). Recently, three recent systematic reviews of the treatment of refugees and asylum seekers resettled in highincome countries have demonstrated the efficacy of psychosocial interventions on PTSD symptoms (Nosè et al, 2017;Thompson, Vidgen, & Roberts, 2018;Turrini, Purgato, Acarturk, & Anttila, 2019).…”
Section: Treatment Of Traumatized Refugeesmentioning
confidence: 89%
“…Evaluating nine studies of cognitive behavioural therapy (CBT) and narrative exposure therapy (NET) with torture survivors, a Cochrane review found no immediate posttreatment effect. In contrast, three NET studies, and a CBT study elicited medium effect sizes on trauma symptoms at six-month follow-up (Patel, Kellezi, & Williams, 2014 ), while a meta-analysis of torture survivors found that psychological interventions significantly reduced PTSD symptoms by the end of treatment, with a small SMD that remained at follow-up (Hamid, Patel, & Williams, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the major ones is that of restricting eligibility for the trial according to population characteristics, discussed under myth 4, but often excluding people with multiple problems, or who are more likely to drop out of psychological care; examples are people with insecure accommodation or undetermined legal status, as is common in torture survivor populations, or who do not speak fluently the language of the rehabilitation service provider. Some RCTs on psychological interventions with torture survivors (see reviews by Hamid et al 2019;Patel et al 2014) have recognised these issues and taken a more inclusive approach to recruitment, not without its own difficulties. Another disadvantage is that the interventions are multi-component -they consist of a series of separate or combined components of presumed therapeutic benefit, delivered by a trained therapist -and no RCT can disaggregate the effects of each component from the others, yet the assumption that they are always synergistic, and to all participants, is rarely tested or even raised as a concern.…”
Section: Myth 3: Efficacy Of Psychosocial Interventions Can Only Be D...mentioning
confidence: 99%
“…Our systematic reviews and meta-analyses (Patel et al, 2014;Hamid et al, 2019; see also Patel et al, 2016) found relatively few studies (restricted to randomised controlled trials); all were of individual psychological 'treatment', usually compared to 'no treatment', and primarily aimed at reducing post-traumatic stress disorder (PTSD), a psychiatric disease category. Benefits of these interventions were few and weak; confidence intervals were wide and methodological biases common, undermining confidence in estimates of 'treatment' effects.…”
Section: Introductionmentioning
confidence: 99%
“… 8 There is limited information about the types of services provided to torture survivors and the outcomes of such services. 9 These services can include the provision of psychological interventions (at individual, family or group level) aiming to change cognitive, emotional or behavioural outcomes, which have been reported to improve the psychological distress of torture survivors. 9 …”
Section: Introductionmentioning
confidence: 99%